Distribution and sampling of Maruca vitrata (Fabricius) (Lep.: Pyralidae) larvae on Lonchocarpus sericeus (Poir) H.B. and K - Atachi, P.; Dannou, E.A.; Arodokoun, Y.D.; Tamo, Manuele (Wiley, 2002)
The spatio-temporal distribution of the pod borer Maruca vitrata was assessed on Lonchocarpus sericeus over a period of 6 months, in order to develop sampling plans and facilitate sampling on this host plant. Lonchocarpus sericeus, one of the preferred alternative host plants of M. vitrata is widely spread in Benin and should therefore be included in the ecological management of the insect. Some experiments were conducted at an ecological site in south Benin, where L. sericeus can be found. The analysis of 17 weekly samples showed that tree canopy did not have a significant effect (P=0.3471) on larval distribution. Significant differences (P=0.0001) were obtained between the sizes of flowers (10, 20, 30 and 40 racemes). Geographical quadrants consisting of the upper east branches, lower east branches, upper west branches and lower west branches did not differ significantly (P=0.8713). The time of infestation of L. sericeus by M. vitrata was investigated by taking samples every 2 days. Data analysis of these samples revealed that L. sericeus was infested at the open flower stage. Temporal distribution of larvae showed the greatest abundance of larvae occurred in June. The index of aggregation was 1.37 with the TAYLOR law and 1.26 with the Iwao procedure. These values showed that the larval dispersion pattern is negative binomial. On this basis, sequential sampling plans were developed and these could permit an accurate estimate of tree data for sampling.